A Connectomic Analysis of the Human Basal Ganglia Network - Cacciola, Alberto; Calamuneri, Alessandro; Milardi, Demetrio; Mormina, Enricomaria; Chillemi, Gaetana; Marino, Silvia; Naro, Antonino; Rizzo, Giuseppina; Anastasi, Giuseppe; Quartarone, Angelo (Frontiers in Neuroanatomy, 2017)
The current model of basal ganglia circuits has been introduced almost two decades ago and has settled the basis for our understanding of basal ganglia physiology and movement disorders. Although many questions are yet to be answered, several efforts have been recently made to shed new light on basal ganglia function. The traditional concept of “direct” and “indirect” pathways, obtained from axonal tracing studies in non-human primates and post-mortem fiber dissection in the human brain, still retains a remarkable appeal but is somehow obsolete. Therefore, a better comprehension of human structural basal ganglia connectivity in vivo, in humans, is of uttermost importance given the involvement of these deep brain structures in many motor and non-motor functions as well as in the pathophysiology of several movement disorders. By using diffusion magnetic resonance imaging and tractography, we have recently challenged the traditional model of basal ganglia network by showing the possible existence, in the human brain, of cortico-pallidal, cortico-nigral projections, which could be mono- or polysynaptic, and an extensive subcortical network connecting the cerebellum and basal ganglia. Herein, we aimed at reconstructing the basal ganglia connectome providing a quantitative connectivity analysis of the reconstructed pathways. The present findings reinforce the idea of an intricate, not yet unraveled, network involving the cerebral cortex, basal ganglia, and cerebellum. Our findings may pave the way for a more comprehensive and holistic pathophysiological model of basal ganglia circuits.